OPTIMASI PROSES SULFONASI LIGNIN MENJADI NATRIUM LIGNOSULFONAT (NaLS) DAN KARAKTERISASI SEBAGAI ADITIF JENIS WATER REDUCING ADMIXTURES (WRA) (Universitas Esa Unggul, 2007)
ABSTRACÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Sodium lignosulfonat (NaLS) is a product that comes from lignin sulfonation process using NaHSO3 as its sulfonation agent. The process aimed to change the polarity of lignin.Â NaLS is classified of an anionic surfactant which has more polar hydrophilic property thanÂ that of lignin. Due to its property, NaLS has more useful as water reducing admixtures(WRA) which has a function as a binder and dispersantÂ in gypsumÂ paste or cement paste. Respon surface method (RSM) was used in optimization of sulfonation process with variation in ratio lignin and NaHSO3, acid value and temperature reaction. The optimum condition was obtained at reaction ratio of 60.6 %, pH 6,3 and temperature at 90 OC, yielded of 72.2 % with the purity of NaLS 80.05 %. NaLSÂ identification used FT-IR and NMR spectroscopy has similar spectrumÂ with Aldrich lignosulfonat (LS-Aldrich) . The physical-chemical properties of NaLS was also similar to lignosulfonate as water reducing admixtures (WRA) which meet the specco Wâ€ 20â€ Standard requirement.Keyword: Lignin, Sulfonation, Natrium lignosulfonat, Surfactant, Water reducing asmixtures, Dispersant